The effect of ski boot flexion stiffness on jump landings in skiing - Kurpiers, N.; Petrone, N.; Wisser, A.; Hansen, J.; Supej, M.; Kersting, U. (Science and Skiing VII, 2018)
Freestyle skiing has become increasingly popular within the last two decades, particularly since the introduction of slope-style skiing at the 2014 Olympic winter games in Sochi. Freestyle skiing is generally performed by both elite and recreational skiers, and is associated with a high incidence of injuries mainly affecting the knee joint (Langran, 2008; Hunter, 1999). In the seasons from 2006 to 2009, almost half of the competitive World Cup freestylers suffered an injury, 32% of which were severe in nature and 27% of which involved the knee joint (Florenes, et al., 2010). The boot-induced anterior drawer (BIAD) effect has been identified as one of the most common injury mechanisms in alpine skiing, specifically in freestyle skiing. It is believed that the risk of a rupture of the anterior cruciate ligament (ACL) is significantly increased in landing situations in freestyle skiing (e.g., moguls or slope style) due to the limited range of movement (ROM) in the anterior direction when bending the legs to absorb a bump or decelerate the upper body after a jump (Gerritsen, et al" 1996; Withrow, et al., 2006; Schaff & Olbert, 1996). Previously, it has been shown that a flexible boot shaft may allow an improvement in skiing technique and reduce the loads on the knee joint when negotiating a mogul course (Kurpiers, McAlpine, & Kersting, 2011). An antecedent study has shown that, at the instant of maximum reaction force application, parameters reflecting joint loading decreased, presumably due to a change in the kinematic strategy of the skier resulting in a more forward-oriented center of mass (COM) and thus a more advantageous position on the ski regarding control and safety. It has not yet been investigated which effects these boots may have on landing technique after aerials which are key elements in competitive mogul skiing and slope-style skiing, respectively. For the current study, the same ski boots with the same modification have been used as in the previous investigation with reduced shaft material and one pivot point at the ankle joint (Kurpiers, McAlpine, & Kersting, 2011). The purpose of this study was to compare landing kinematics after a jump with a conventional ski boot and a modified ski boot that allows for a distinctly greater forward lean. It was hypothesised that the joint angles increase in the more flexible condition.